Analisis Reflektif: Instructional & Nurturant Effect Pada Implementasi Pembelajaran STEAM Melalui Lesson Study di SDN 11 Peguyangan - Juniayanti, Dewi; Putra Nugraha, Dewa Made Dwicky (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research aims to determine the instructional & nurturant effects on the implementation of STEAM learning in lesson study activities at SDN 11 Peguyangan. This research used a qualitative descriptive research approach. The subjects of this research were class V and VI students, the school principal, and 4 partner teachers. The themes revealed in this research are the instructional effect in the form of increasing students' critical thinking abilities, and the nurturan effect in the form of changes in behavior, habits, and other symptoms experienced by research subjects. The primary data sources for this research were student activities observation and their learning outcomes, as well as notes on reflections from teachers and school headmaster. The data was collected by using observation and documentation techniques. Data were analyzed by using qualitative analysis techniques. The results of this research include; 1) The instructional effect of implementing STEAM learning through lesson study which show that students' critical thinking skills at SDN 11 Peguyangan was increasing. and 2) nurturing effect of this program on students; a) not easily satisfied with the results of their work, b) freely in expressing feelings, c) increased enthusiasm for learning, self-confidence and ability to collaborate. Nurturant effects on teachers include; a) pedagogical insight increases, b) creates a culture of collaboration between teachers, c) more motivated to always implement innovative student-centered learning, d) literacy activities for exploring various learning strategies become more intense, and e) get used to reflecting at the end learning. Meanwhile, school principals include; a) better able to understand the characteristics of teachers and needs in the classroom, b) motivated to develop programs that focus on developing teacher competency, and c) openness to building wider networks/collaboration with external parties